Design of Sensor-Based Semi-Automatic Car Wash System Prototype and it’s Gear Box Conveyor Calculation - E. M. Saputra; R. M. Z. H. Putra; W. A. S. Putra; M. Miftakhurrohman; R. D. Issafira (BIOMEJ, 2023)
The rapid and widespread development of science and technology (IPTEK). Particularly in the automotive industry has encouraged the development of the automotive industry, especially in four-wheeled vehicles or also known as cars. Given the number of vehicles that are still quite a lot, maintenance, care and repair must be carried out for the smooth running of the car's work process so that the car's work process runs smoothly. One of them is the system of car washing. In the process of washing a car, the uses of human power (manual) still predominant. This automatic car wash system is the perfect solution to save time and effort. Based on this, a designed small-scale sensor based semi-automatic car wash miniature was made. Supporting components are needed so that the automatic car wash system can work according to the desired design, including Ultrasonic sensors, DC motors, dynamo motors, Water Pumps, 12V fans. The main objective of this simulation is the development of criteria to design and build a car wash of this type-high real way to solve the challenges of automation. The research results show that the proposed method is in process control not only increases productivity, speed, accuracy and safety, but also reduces the time and cost of washing dynamic vehicle models.